Latent fingermark development using low-vacuum vaporization of ninhydrin. (December 2015) - Chen, Chun-Chieh; Yang, Chao-Kai; Liao, Jeh-Shane; Wang, Sheng-Meng
Highlights: A homemade fume hood with vacuum and heating control system is introduced. Latent marks were effectively developed by vaporizing solid ninhydrin. Latent marks on thermal paper were successful developed without discoloration. This study provides application for developing latent marks without using solvents. Abstract: The vacuum technique is a method of vaporizing a solid material to its gas phase, helping deposit reagents gently on target surfaces to develop latent fingermarks. However, this application is rarely reported in the literature. In this study, a homemade fume hood with a built-in vacuum control system and programmable heating system designed by the Taiwan Criminal Investigation Bureau is introduced. Factors that affect the instrument's performance in developing fingermarks are discussed, including the quantity of chemicals for vaporization, heating program arrangement, and paper of different materials. The results show that fingermarks are effectively developed by vaporizing solid ninhydrin. This would be an alternative application in selecting a solvent-free method for protecting the environment and reducing health hazards in the lab. In terms of the heating program, the result indicates that under a low-vacuum condition (50 mTorr), 80–90°C is a suitable temperature range for ninhydrin vaporization, allowing ninhydrin to be vaporized without bumping and waste. In terms of the performance on different material papers, this instrument demonstrates its capacity by developing latent fingermarks on thermal paper without discoloration or damaging the original writing, and the same results are also observed on Taiwan and United States banknotes. However, a coherent result could be hardly obtained using the same vaporization setting because different banknotes have their own surface features and water absorption ability or other unique factors may influence the effect of ninhydrin deposition. This study provides a reliable application for developing latent fingermarks without using solvents, and it is also expected to contribute to environmental protection along with the trend of green chemistry technology.